Systemic and mucosal stress responses of Atlantic salmon (Salmo salar) to peracetic acid - Soleng, Malene (UiT The Arctic University of Norway, 2019)
Infectious diseases are still a major problem in salmon aquaculture despite several attempts on developing prophylactic measures. Amoebic gill disease (AGD) is considered a growing threat in Norwegian salmon aquaculture. It has increased in prevalence and geographic distribution in the last years, resulting in considerable economic losses. Current treatments (i.e., freshwater and hydrogen peroxide bathing) are not optimal as they have both practical and welfare issues. It is, therefore, necessary to find new treatment alternatives. Peracetic acid (PAA) is under consideration as a potential treatment against AGD, but it is vital in the development of new chemotherapeutic measures that the consequences to the health and welfare of fish be identified. The overall aim of this thesis was to evaluate the systemic and mucosal stress responses of Atlantic salmon (Salmo salar) post smolts to peracetic acid. In Trial 1, salmon were first exposed to different nominal concentrations (0, 0,6 and 2,4 ppm) of PAA for 5 minutes, followed by a re-exposure to the same concentrations for 30 min 2 weeks later. Sampling was performed before exposure, 2 h, 48 h, and 2 w after exposures on both occasions. In Trial 2, salmon were subjected to crowding stress prior to PAA exposure at 4,8 ppm, double than the highest concentration tested in Trial 1. The fish were sampled before exposure, 1 h, 4 h, and 2 w after exposure. The treatments in both trials did not dramatically affect the overall external welfare status of fish. Both systemic and mucosal stress indicators were affected by the treatments at varying levels, and it was apparent that the fish were able to mount an appropriate response to the physiological demands of PAA exposure. In particular, the cortisol levels increased in the early hours after exposure, then followed by a rapid decrease and was back at baseline levels 2 weeks post-exposure. Prior exposure history to PAA did not markedly affect the stress responses of fish when re-exposed to PAA. Crowding stress before PAA ...